Beyond the Big Five: The mediating role of goal orientation in the relationship between core self-evaluations and academic performance. Issue 3 (November 2016) - Debicki, Bart J.; Kellermanns, Franz W.; Barnett, Tim; Pearson, Allison W.; Pearson, Rodney A.
Abstract: In this paper, we investigate the impact of core self-evaluations on academic performance. We also test several hypotheses that describe a potential mediating effect of three types of goal orientation on the above relationship. The model developed in this paper is statistically tested on a sample of 307 college students. The results indicate that students who perceive themselves as competent, capable and worthy of success (i.e. demonstrating positive core self-evaluations) achieve superior academic performance. Furthermore, the avoid performance type of goal orientation partially mediates the relationship between core self-evaluations and academic performance. Prove performance goal orientation is associated with better academic performance, but is not influenced by core self-evaluations. Learning goal orientation, which is characteristic of individuals exhibiting an intrinsic desire to improve their competence, does not have a significant impact on academic performance. The main contribution of this study lies in showing the positive impact of high core self-evaluations on academic performance and investigating the mechanism through which this relationship develops, namely the mediating effects of goal orientation. Highlights: We investigate the impact of core self-evaluations on academic performance. We study the mediating effect of three types of goal orientation. Students with positive core self-evaluations achieved superior academic performance. Avoid performance goal orientation played a partially mediating role. Prove performance goal orientation improved academic performance. Learning goal orientation did not result in better academic performance.